Malaysian public interest in common medical problem: a 10-year Google Trends analysis - Kow, Ren Yi; Mohamad Rafiai, Norfazilah; Ahmad Alwi, Akmal Azim; Low, Chooi Leng; Siron @ Baharom, Khairul Nizam; Zulkifly, Ahmad Hafiz; Zakaria@Mohamad, Zamzuri; Awang, Mohamed Saufi (Cureus, Inc., 2022)
Background An analysis of internet search has been performed to evaluate the public interest in health problems. Google Trends (GT) serves as a free platform to analyse the search traffic for specific terms in the Google search engine. This observational study aims to investigate the trend of Malaysian population in using the Google search engine on common medical problems and explore the geographical influence on the language used.